2020
DOI: 10.12688/f1000research.21564.1
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of Ki-67 as a predictor of lymph node metastasis in penile cancer patients

Abstract: Introduction: Penile cancer is a moderately common malignancy in developing countries. Metastasis to regional lymph nodes is an essential factor in a patient’s prognosis, as its occurrence predicts poor patient prognosis. As micro-metastasis occurs in more than 25% of cases, the need for more accessible diagnostic tools is necessary. Ki-67 is commonly used as a marker of proliferation associated with tumor grade and lymph node metastasis. Methods: Samples were taken from penile cancer patients between 2013 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The antioxidant and tumor sup-pressor superoxide dismutase (SOD2) overexpression (overexpression=present in >50% of cells; seen in 44.8% of penile SCCs) was also predictive of lymph node involvement: 52.8% of patient with nodal involvement had the above criteria for overexpression compared to 24.6% with <50% of cells overexpressing (10). Warli et al recently reported that overexpression (>20% of nuclei) of the nuclear proliferative protein Ki-67 is associated with increased movement of SCC of the penis to inguinal lymph nodes independent of tumor stage and grade (21). Diffuse PD-L1 expression is significantly predictive, which serves as a clinically relevant marker because of recent advancements targeting PD-L1 with immunotherapeutic agents (17).…”
Section: Biochemical Factorsmentioning
confidence: 99%
“…The antioxidant and tumor sup-pressor superoxide dismutase (SOD2) overexpression (overexpression=present in >50% of cells; seen in 44.8% of penile SCCs) was also predictive of lymph node involvement: 52.8% of patient with nodal involvement had the above criteria for overexpression compared to 24.6% with <50% of cells overexpressing (10). Warli et al recently reported that overexpression (>20% of nuclei) of the nuclear proliferative protein Ki-67 is associated with increased movement of SCC of the penis to inguinal lymph nodes independent of tumor stage and grade (21). Diffuse PD-L1 expression is significantly predictive, which serves as a clinically relevant marker because of recent advancements targeting PD-L1 with immunotherapeutic agents (17).…”
Section: Biochemical Factorsmentioning
confidence: 99%
“…Protein Ki-67 is considered a good indicator of cell proliferation and correlates with tumor growth [ 13 , 14 ]. Cell proliferation is one of the main factors in the biological mechanisms of oncogenesis; therefore, several studies have shown that the activity of cell proliferation is linked with the prognosis of certain cancers such as cervical cancer, breast cancer, carcinoma of the penis, and larynx [ 15 - 18 ]. Ki-67 protein has also been reported to correlate with tumor aggressiveness and has prognostic and predictive value in breast and colon cancer, melanoma, and lymphoma patients [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%